Penerapan Model Pembelajaran Kooperatif Tipe Teams Games Tournament (TGT) Menggunakan Media Kartu dan Ular Tangga pada Hasil Belajar IPA Fisika Siswa - Roza, Media; Rahman, Roza (Universitas Islam Negeri Imam Bonjol Padang, 2017)
The objective of this study is to determine students’ learning outcomes physic between Instruction Based Learning model using TGT type of media snake ladder compared to conventional learning in class VIII MTsN 1 Lubuk Basung. The hypothesis formulated in this research is